Incidence and Risk Factors of Postoperative Mortality and Morbidity After Elective Versus Emergent Abdominal Surgery in a National Sample of 8193 Patients With Cirrhosis. Issue 4 (October 2021) - Johnson, Kay M.; Newman, Kira L.; Green, Pamela K.; Berry, Kristin; Cornia, Paul B.; Wu, Peter; Beste, Lauren A.; Itani, Kamal; Harris, Alex H. S.; Kamath, Patrick S.; Ioannou, George N.
Abstract : Objective: To describe the incidence and risk factors for mortality and morbidity in patients with cirrhosis undergoing elective or emergent abdominal surgeries. Background: Postoperative morbidity and mortality are higher in patients with cirrhosis; variation by surgical procedure type and cirrhosis severity remain unclear. Methods: We analyzed prospectively-collected data from the Veterans Affairs (VA) Surgical Quality Improvement Program for 8193 patients with cirrhosis, 864 noncirrhotic controls with chronic hepatitis B infection, and 5468 noncirrhotic controls without chronic liver disease, who underwent abdominal surgery from 2001 to 2017. Data were analyzed using random-effects models controlling for potential confounders. Results: Patients with cirrhosis had significantly higher 30-day mortality than noncirrhotic patients with chronic hepatitis B [4.4% vs 1.3%, adjusted odds ratio (aOR) 2.80, 95% confidence interval (CI) 1.57–4.98] or with no chronic liver disease (0.8%, aOR 4.68, 95% CI 3.27–6.69); mortality difference was highest in patients with Model for End-stage Liver Disease (MELD) score ≥10. Among patients with cirrhosis, postoperative mortality was almost 6 times higher after emergent rather than elective surgery (17.2% vs. 2.1%, aOR 5.82, 95% CI 4.66–7.27). For elective surgeries, 30-day mortality was highest after colorectal resection (7.0%) and lowest after inguinal hernia repair (0.6%). Predictors of postoperative mortality included cirrhosis-related characteristics (high MELD score, low serum albumin, ascites, encephalopathy), surgery-related characteristics (emergent vs elective, type of surgery, intraoperative blood transfusion), comorbidities (chronic obstructive pulmonary disease, cancer, sepsis, ventilator dependence, functional status), and age. Conclusions: Accurate preoperative risk assessments in patients with cirrhosis should account for cirrhosis severity, comorbidities, type of procedure, and whether the procedure is emergent versus elective. Abstract : Supplemental Digital Content is available in the text